E-Commerce Ecosystem in India: Opportunities, Challenges, and Growth Drivers - Shailendra Kumar (AG Volumes, 2025)
E-commerce refers to the buying and selling of products and services over the internet, including the necessary data and monetary transfers to complete the transactions. It is commonly known as online or electronic commerce. India's e-commerce industry is growing quickly. The number of firms in our country is expected to rise significantly, according to e-commerce estimates. A increasing number of people using mobile devices to access the internet has contributed to the rapid expansion of Indian e-commerce in recent years. This article addressed the Opportunities, Challenges, and Growth Drivers in E-Commerce Ecosystem in India. This concluded that India’s e-commerce sector is expanding rapidly due to improved digital infrastructure, changing consumer behavior, and government support. Despite challenges like data security and low digital literacy, better logistics and technology are driving growth. Complementing traditional retail, fostering innovation, and strengthening rural connectivity can help India become a global e-commerce leader